The economic impact of workforce disruptions on the output during Covid-19 pandemic - Heizlyn Amyneina Hamzah,; Mohd Yusof Saari,; Muhammad Daaniyall Abd Rahman,; Chakrin Utit, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper examines the economic impact of workforce disruptions on the output, final demand and Gross Domestic Product by applying an extended input-output (I-O) model. In the extended I-O model, workforce disruptions are measured and modelled in two perspectives: loss of employment (LOE) and inter-industry disruptions that limit the number of workers in the production. Results show that the inter-industry disruption / supply shock is likely to give a tremendous impact compared to the LOE. Moreover, the level of economic impact is also influenced by the level of economic integration among sectors. In this regard, the more integrated a sector with the high-risk sectors, the more impacted the sector is. In conclusion, the results suggest the need for balancing the economic and health risks to ensure that the welfare of people is protected.